Terjemah The Representation Of Translating Quranic Verses Based On Javanese Literature In The Form Of Tembang Macapat - Hidayat, Kun; Lutfianto, Lutfianto; Bustam, Betty Mauli Rosa; Shalihin, Rahmat Ryadhush (ZAD Al-Mufassirin, 2024)
The approach of Koran translation using Javanese literature needs to be represented in order to increase the potential for better acceptance of Koran translation by the Javanese community. The purpose of this study is to represent some Qur'anic verses to be translated using several types of tembang macapat, including tembang pangkur, tembang maskumambang, tembang dhandhanggula, and tembang megatruh. The method in this study uses a descriptive qualitative type of Koran verses that have been translated into Javanese based on the rules of tembang macapat, to then be analyzed using a content analysis approach to the rules in tembang macapat, as well as the suitability of the rules of guru gatra, guru lagu, and guru wilangan. The results of this research become one of the alternatives to the representation of how the Koran is translated into tembang macapat, as when translated it needs to contain a translation that does not violate the core meaning of the verse, and Javanese grammar that conforms to the level of use of krama and ngoko language, but still follows the rules of guru gatra, guru lagu, and guru wilangan in each type of tembang macapat.